Endoscopic full-thickness resection with defect closure using an over-the-scope clip for gastric subepithelial tumors originating from the muscularis propria - Guo, Jintao (Surg Endosc, 2015)
BACKGROUND: Endoscopic full-thickness resection (EFTR) is a mini-invasive technique for gastric subepithelial tumors originating from the muscularis propria, which enables a full-thickness resection of tumors and can provide a complete basis for pathological diagnosis. Gastric fistula closure after EFTR is a challenge for endoscopists. In this study, we introduced EFTR with fistula closure using the over-the-scope clip (OTSC) system for gastric subepithelial tumors originating from the muscularis propria. OBJECTIVES: To evaluate the feasibility and safety of fistula closure with OTSC by a retrospective analysis on the cases of EFTR with defect closure using OTSC for gastric subepithelial tumors originating from the muscularis propria in our hospital. METHODS: The patients were selected who underwent EFTR for gastric subepithelial tumors originating from the muscularis propria (tumor diameter ≤2 cm) in our hospital from October 2013 to March 2014. After a full-thickness resection of tumors, the bilateral gastric mucous membranes of defect were clamped using twin graspers and then drawn into the transparent cap of OTSC, and the OTSC was released to close the defect after full suctioning. The success rate of defect closure with OTSC was observed, and the endoscopic follow-up was performed at 1 week, 1 and 6 months after operation to check OTSC closure. RESULTS: Totally 23 patients were included into the study. The full-thickness resection rate of gastric tumors in the muscularis propria was 100 % (23/23), the success rate of defect closure was 100 %, and the average time of defect closure was 4.9 min (range 2–12 min). All patients experienced no postoperative complications such as bleeding and perforation. The postoperative follow-up time was 1–6 months (mean 3 months), and no OTSC detachment was found. CONCLUSIONS: OTSC can be used to perform EFTR with defect closure for gastric tumors in the muscularis propria (tumor diameter ≤2 cm). It is simple, convenient, safe and effective. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00464-015-4076-2) contains supplementary material, which is available to authorized users.